UK surveillance of childhood idiopathic intracranial hypertension (IIH). (24th May 2012) - Matthews, YY; Dean, F; Matyka, K; McLachlan, K; Solanki, G; Lim, MJ; White, C; Kennedy, C; Whitehouse, W
Abstract : Aims: IIH is the rare condition of intracranial hypertension without identifiable pathology. Associated headache and procedures to treat it can be distressing and the papilloedema has an associated risk of blindness. Previous childhood IIH epidemiological data was limited to hospital-based retrospective case series. This study reports a contemporary national annual incidence of childhood IIH, associated risk factor of obesity, current management and outcome at one-year following diagnosis. Methods: Monthly notification for 25 months from July 2007 of newly diagnosed IIH cases aged 1-16 years through British Paediatric Surveillance Unit reporting scheme by all reporting UK paediatricians. One-year post IIH diagnosis outcome data was collated. The IIH case definition comprised: At least two key features: ▶ Symptoms of raised intracranial pressure and/or visual symptoms; ▶ Papilloedema; ▶ Opening cerebrospinal fluid pressure (CSF) above 20 cm H2 O; ▶ and all essential criteria; ▶ Normal consciousness level; ▶ CT/MRI brain±MR/CT venography does not reveal a structural cause such as ventricular dilatation, cerebral or vascular lesion, venous sinus thrombosis; ▶ Normal CSF contents; Results: 379 notifications identified 185 (93-confirmed, 92-probable) cases of childhood IIH. 85% (158/185) submitted one-year post diagnosis data. Median age at diagnosis was 12 years. 68% (125/185) were female. 60% (105/174) were obese (BMI ≥ 98th centile). Within this cohort, 81% (150/185) received medical treatment (s), 19% (35/185) had 3 or more lumbar punctures and 13% (24/185) underwent neurosurgery. Visual acuity and/or field deficits were present in 33% (61/185) at diagnosis and 10% (16/158) at one-year follow up. Estimated UK annual incidence is 0.8 (1.0 for girls, 0.5 for boys) per 100, 000 child population aged 1-16 years. Conclusions: An average of 60 girls and 29 boys were diagnosed with childhood IIH each year in the UK. Obesity is the commonest association. The majority received medical treatment (s), a reasonable proportion needed repeated lumbar punctures and neurosurgery. Despite interventions one-in-ten had reported visual deficits at one-year post IIH diagnosis. This study highlights the urgent need to generate well-designed multicentre controlled trials to inform the efficacy of current non-evidenced based medical and surgical treatments in childhood IIH.